Phytochemicals Showing Antiangiogenic Effect in Pre-clinical Models and their Potential as an Alternative to Existing Therapeutics - Senrung, Anna; Tripathi, Tanya; Aggarwal, Nikita; Janjua, Divya; Yadav, Joni; Chaudhary, Apoorva; Chhokar, Arun; Joshi, Udit; Bharti, Alok C. (Current Topics in Medicinal Chemistry, 2024)
Angiogenesis, the formation of new blood vessels from a pre-existing vascular network, is an important hallmark of several pathological conditions, such as tumor growth and metastasis, proliferative retinopathies, including proliferative diabetic retinopathy and retinopathy of prematurity, age-related macular degeneration, rheumatoid arthritis, psoriasis, and endometriosis. Putting a halt to pathology-driven angiogenesis is considered an important therapeutic strategy to slow down or reduce the severity of pathological disorders. Considering the attrition rate of synthetic antiangiogenic compounds from the lab to reaching the market due to severe side effects, several compounds of natural origin are being explored for their antiangiogenic properties. Employing pre-clinical models for the evaluation of novel antiangiogenic compounds is a promising strategy for rapid screening of antiangiogenic compounds. These studies use a spectrum of angiogenic model systems that include HUVEC two-dimensional culture, nude mice, chick chorioallantoic membrane, transgenic zebrafish, and dorsal aorta from rats and chicks, depending upon available resources. The present article emphasizes the antiangiogenic activity of the phytochemicals shown to exhibit antiangiogenic behavior in these well-defined existing angiogenic models and highlights key molecular targets. Different models help to get a quick understanding of the efficacy and therapeutics mechanism of emerging lead molecules. The inherent variability in assays and corresponding different phytochemicals tested in each study prevent their immediate utilization in clinical studies. This review will discuss phytochemicals discovered using suitable preclinical antiangiogenic models, along with a special mention of leads that have entered clinical evaluation.
Keywords: Antiangiogenic phytochemicals